2015
DOI: 10.1038/ejcn.2015.131
|View full text |Cite
|
Sign up to set email alerts
|

A review of European guidelines on periconceptional folic acid supplementation

Abstract: Strong evidence that folic acid (FA) prevents the majority of cases of neural tube defects (NTDs) has led to national organisations developing guidelines for women concerning periconceptional supplementation. In Europe, there is evidence of national variations in the incidence of NTDs, with a recent Irish study reporting an increase in the rate. This review compares the periconceptional FA supplementation guidelines between the different countries in Europe. An online search of country-specific guidelines prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 22 publications
1
46
0
2
Order By: Relevance
“…Fourthly, parous women should be reminded during late antenatal or postpartum visits about the importance of folic acid supplement use before possible subsequent pregnancies. Additionally, a potential, but controversial option would be to consider food fortification with folate as some authors have suggested [9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourthly, parous women should be reminded during late antenatal or postpartum visits about the importance of folic acid supplement use before possible subsequent pregnancies. Additionally, a potential, but controversial option would be to consider food fortification with folate as some authors have suggested [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Recommendations for peri-conceptional folic acid supplementation vary in Europe [9]. In Norway, all women planning a pregnancy or who may become pregnant, are recommended to use folic acid supplements (0.4 mg/day) at least from one month before conception until three months gestation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Maternal supplementation with folic acid is widely recommended to all women of childbearing age, especially to reduce the risk of neural tube defects [66,67]. According to recent studies, folic acid supplementation during pregnancy should also reduce the risk of congenital heart disease and support proper development of the placenta [68].…”
Section: Micronutrientsmentioning
confidence: 99%
“…This recommendation is based on clinical experience, descriptive studies, or reports of expert committees rather than on properly randomized controlled trials. That is, the opinions of respected authorities have been considered satisfactory enough to recommend folic acid supplementation in women of childbearing age [13,14]. The aforementioned guidelines also emphasize that folic acid/ multivitamin supplementation is needed to achieve the serum concentrations that are required to provide protection against neural tube defects.…”
Section: Discussionmentioning
confidence: 99%